A morphological, morphometric and histochemical study of the oviduct in pregnant and non‐pregnant females of the plains viscacha (Lagostomus maximus). (28th December 2012) - Flamini, Mirta A.; Barbeito, Claudio G.; Portiansky, Enrique L.
Abstract The oviduct is a very thin organ with a very tortuous appearance. It is divided into three segments: the infundibulum, the ampulla and the isthmus. Particularly, the oviduct of the viscacha lacks the intramural portion described in other species. The mucosa shows longitudinal pleats. The free edge of the infundibulum ends as small fimbriae that are of variable length and do not completely cover the ovary. The proportion of ciliated and secretory epithelial cells varied both in relation to the segments of the oviduct analysed and to the physiological state (anoestrus, follicular phase, early pregnancy and late pregnancy). The glycocalix and the apical region of the superficial epithelial cells are PAS and alcian‐blue positive. The muscular layers vary in thickness in different regions. Some lectins such as UEA‐1 and DBA showed variations in the binding pattern during the different physiological stages analysed whereas RCA‐1and WGA had a very stable pattern.